2004
DOI: 10.1046/j.1365-2923.2004.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching anatomy without cadavers

Abstract: Evidence relating to the effect on medical learning by students not exposed to cadavers is scant, and plainly opportunities will now arise through our programme to gather such evidence. We anticipate that this discussion paper will contribute to an ongoing debate, in which virtually all previous papers on this topic have concluded that use of cadavers is essential to medical learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
445
1
43

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(504 citation statements)
references
References 39 publications
15
445
1
43
Order By: Relevance
“…Our study also found that reflection about death and dying, as well as feelings of empathy toward the body donor, reduced over time. The latter finding supports the opinion, as has been expressed by McLachlan et al (2004), that dissection in the gross anatomy course is not suitable for encouraging an early development of empathy. Our study results suggest that students' perceptions of gaining professional competencies may influence their evaluation of course value, over and above the acquisition of anatomical knowledge.…”
Section: Professional Competenciessupporting
confidence: 79%
See 2 more Smart Citations
“…Our study also found that reflection about death and dying, as well as feelings of empathy toward the body donor, reduced over time. The latter finding supports the opinion, as has been expressed by McLachlan et al (2004), that dissection in the gross anatomy course is not suitable for encouraging an early development of empathy. Our study results suggest that students' perceptions of gaining professional competencies may influence their evaluation of course value, over and above the acquisition of anatomical knowledge.…”
Section: Professional Competenciessupporting
confidence: 79%
“…In the recent past, some American universities have abstained from dissection (Collins et al, 1994). Similar trends can be observed in Europe (McLachlan et al, 2004) and are currently being discussed at German universities. To continue or to abolish laboratory dissection as part of the medical curriculum is a major decision whose taking requires an understanding of the course's direct and hidden teaching objectives as well as the influence of dissection on achieving superordinated curricular goals.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…These challenges have been faced with varying success by a number of medical schools that experimented with the design of their anatomy course . One general approach has been to use the radiographic, medical, and surgical applications of anatomy to guide the structure and content of the course (McLachlan et al, 2004;Drake, 2007;Haubert et al, 2009). Examination of the efficacy of these approaches has been limited to preliminary studies.…”
Section: Introductionmentioning
confidence: 99%
“…The value of dissection classes as a teaching format lies in the fact that it provides a 3D view on human anatomy including tactile learning experiences. It enables elaboration of knowledge already acquired in lectures and study books and it provides an overall perspective of anatomical structures and their mutual relations in a whole organism [7]. The cadaver-based learning has seen decline due to practical and cost issues (see Figure 2).…”
Section: Traditional Methodologiesmentioning
confidence: 99%